Development of a Web-Based Sales Information System for Benson Bakery Using the Waterfall Model - Juliana, Juliana; Khalidy, Furqan; Lubis, Zulkarnain (Devitara Innovations, 2025)
The rapid development of information technology has encouraged many businesses, including small and medium enterprises, to adopt information systems for business management. Benson Bakery, a bakery and pastry business, still relies on manual record-keeping, leading to delayed reports, data loss, and order inaccuracies. This study aims to design a web-based sales information system to improve operational efficiency and service quality. The system development method used is the Waterfall model, which includes the stages of requirement analysis, design, implementation, testing, and maintenance. The result is an integrated system capable of managing product, order, and report data in real-time. The implementation of this system is expected to optimize business processes at Benson Bakery and enhance customer satisfaction.